Strategy for Resolving Gender Conflict in the Household for Women Industrial Workers - Inderasari, Elen; Giyoto, Giyoto (Sawwa: Jurnal Studi Gender, 2024)
Poverty forced most females to have double roles as housewives and workers. It happened to help the husbands look for a good living. This research aimed to describe the strategies for female industrial workers in Surakarta to resolve gender conflict in a household. This research used qualitative method to describe the data retrieved by interview technique using social role theory to find out the existence of double role conflict, kinds of conflicts, and strategies in resolution of the gender role conflict from the respondents in the regions of Surakarta, Boyolali, Sragen, Wonogiri, and Sukoharjo by referring to the patterned social behavior, social identity, and shared social expectations. This research uncovered the existence of various conflicts among female workers i.e. working hours, household chores, relationship communication between husband and wife (biological relationship), and childcare. Furthermore, this research also found the strategies used by housewives in facing conflicts, including division of role as head of the family, division of working hours, parenting arrangement, family biological time arrangement, and social community. Regarding the findings, this research provided female industrial workers with several alternative solutions to help them divide their time for professionally working in domestic and public affairs.